Prevalence and familial predictors of suicidal behaviour among adolescents in Lithuania: a cross-sectional survey 2014 - Apolinaras Zaborskis; Dainora Sirvyte; Nida Zemaitiene (BMC, 2016)
Abstract Background In the past decades Lithuania has been experiencing a very high suicide rate among young people and there are scarce data on the role of the family in shaping these people suicidal behaviour. This study investigated the prevalence of suicidal ideation and attempts, as well as their association with a range of familial factors in a representative sample of Lithuanian adolescents. Methods Study subjects (N = 3572) were adolescents aged 13- and 15-years from the schools in Lithuania who were surveyed in Spring 2014 according to the methodology of the cross-national Health Behaviour in School-aged Children (HBSC). A standard HBSC international questionnaire was translated into Lithuanian and used anonymously to obtain information about suicidal behaviour (stopped doing activities, considered suicide, planned suicide, and suicide attempts) and family life (family structure, quality of communication in family, parental monitoring and bonding, parenting style, family time, etc.). Logistic regression was used to assess association between suicidal behaviours and familial variables. Results Forty three percents of surveyed adolescents reported presence of emotions that stopped doing activities during the last 12 months, 23.8 % seriously considered attempting suicide, 13.7 % made a suicide plan, 13.2 % attempted suicide, and 4.1 % needed treatment because of suicide attempt in the previous year. Adolescents from non-intact families reported more suicidal ideation (OR ranged from 1.32 to 1.35, P < 0.05) and more suicide attempts (OR = 1.70, 95 % CI 1.38-2.09, P < 0.001). Among adolescents from intact families, some manisfestations of suicidal behaviour were significantly associated with low satisfaction in family relationships, low father's and mother's emotional support, low mother's monitoring, low school-related parental support, authoritarian-repressive father's parenting style and permissive-neglectful mother's parenting style, but rare family time together and rare electronic media communication with parents were inversely associated with suicidal behaviour. The boys, 15-year-olds and adolescents who indicated often activities together with their families were more likely than their counterparts to report suicide attempts treated by a doctor or nurse. Conclusion The young people of Lithuania are at particular risk for suicides. A non-intact family structure and weak family functioning are significant predictors of suicidal ideation and attempts among adolescents of Lithuania. It is essential to consider family life practices in planning intervention programs for prevention of suicides among adolescents.